The ethics of cultural studies - Zylinska, Joanna, 1971- (Continuum, 2005)
Ethical questions feature prominently on todayGÇÖs cultural andpolitical agendas. The Ethics of Cultural Studies presents an ethicalmanifesto for Cultural Studies, an exploration of its current ethicaland political concerns, and of its future challenges. The book is concerned with ethics in the material world, and drawson examples as diverse as cloning and genetics, asylum andimmigration, experiments in plastic surgery and in electronic anddigital art, memories of the Holocaust, September 11th, and mediarepresentations of violence and crime. The Ethics of Cultural Studies is a groundbreaking int.